Asthmatic Therapy Expert System (ATES) - Lily Marlia, Abdul Latif (2008)
Due to striking increases of death caused by asthma illness, effective actions should be taken in order to overcome the problem. As there are no cure for asthma but there are chances for asthmatic patients to treat the illness. However, in order to get a better asthma-related quality of life, patients need to control or to manage their asthma with care and strictly. Therefore, it is important to provide a system that can help the patient to manage their asthma which can recognize level of asthma according to its severity. The project's objective is to develop a prototype that suggesting homecare treatment either towards conventional asthma medication or Islamic approach by acquitting knowledge from human expert (medical doctors) and from documents (medical books, journals, reports etc). The project used rapid prototyping as methodology to guide throughout the process from initial specification of the project until the evaluation stage in order to make sure all requirements have been met. As a result, the prototype is successfully being built and based on the user testing that have been conducted, users are fully satisfied with the prototype and they are willing to use the system to help them managing their asthma illness.